A review on cloud based knowledge management in higher education institutions - Ahmad Shukri Mohd Noor; muhammad younas; Muhammad Arshad (Institute of Advanced Engineering and Science, 2019)
Knowledge Management (KM) is widely discussed by researcher and attracts many enterprisers to extract, dispense and use information in a systematic way under Knowledge Management System (KMS). New technology adoption within the knowledge management system is one of the core issue, identified by researcher and underlined as future research agenda. Cloud computing becomes the most adoptable choice for enterprisers to reduce infrastructure and maintenance cost by shifting business on the cloud. Higher Education Institutions (HEIs) are more enthusiastic about knowledge management due to its primary goal of knowledge creation and sharing. Cloud based knowledge management attract higher education institutions by changing the educational method and objectives due to innovative trends in technology. This exploratory research based on literature review for cloud-based knowledge management, targeting higher education institutions. This study highlights the benefits and challenges associated with cloud-based knowledge management system and its impact on knowledge.